Herbie Hancock possibilities - Hancock, Herbie 1940-; Dickey, Lisa (Viking, 2014)
"The long-awaited memoir by one of the most influential and beloved musicians of our time. In Herbie Hancock the legendary jazz musician and composer reflects on a thriving career that has spanned seven decades. A true innovator, Hancock has had an enormous influence on both acoustic and electric jazz, R&B and hip-hop, with his ongoing exploration of different musical genres, winning fourteen Grammy awards along the way. From his beginnings as a child prodigy to his work in Miles Davis's second great quintet; from his innovations as the leader of his own groundbreaking sextet to his collaborations with everyone from Wayne Shorter to Joni Mitchell and Stevie Wonder; Herbie Hancock reveals the method behind Hancock's undeniable musical genius. Hancock shares his musical influences, colorful behind-the-scenes stories, his long and happy marriage, and how Buddhism inspires him creatively and personally. Honest, enlightening, and as electrifyingly vital as the man who wrote it, Herbie Hancock promises to be an invaluable contribution to jazz literature and a must-read for fans and music lovers"..